Antivirals and monoclonal antibody combination therapy in haematological patients in the omicron era - Serena Vita; Emanuela Giombini; Patrizia De Marco; Martina Rueca; Cesare Ernesto Maria Gruber; Alessia Beccacece; Laura Scorzolini; Valentina Mazzotta; Carmen Pinnetti; Priscilla Caputi; Daniele Focosi; Enrico Girardi; et al. (Mediterranean Journal of Hematology and Infectious Diseases)
Abstract: Im We describe here a single-center case series of 27 IC COVID-19 inpatients (mostly with haematological disorders) treated with a combined therapy based on tixagevimab/cilgavimab (T/C) plus small-molecule antivirals (AV), between April 1 2022 and November 30 2022.